Optimal Design of Single-stage Double-arc Spiral Bevel Gear Nutation Reducer - Zheng Lin; Ligang Yao; Tongke Su; Zheng Sun (Jixie chuandong)
According to the nutation motion principle，a new single-stage double circular-arc spiral bevel gear nutation reducer with simple structure and large transmission ratio is designed， and its transmission ratio calculation formula is obtained. With the minimum volume of the nutation reducer as the objective function，an optimization mathematical model is established with 4 design variables and 12 optimization constraints，and the relevant parameters of the single-stage nutation bevel gear are obtained. According to the optimized parameters of gear， the three-dimensional model of the nutation bevel gear is established，and its finite element loading strength is analyzed. The results show that the contact area of single-stage nutation bevel gear is large because there are many teeth and concave-convex tooth surfaces in contact at the same time，the Mises stress distribution on the internal and external bevel gears is uniform，but the stress value at the top of the small end of the external bevel gear is larger. The research results are of great significance to the further improvement of single-stage double circular-arc spiral bevel gear nutation reducer.